Flattening the Illiquidity Curve: Retail Trading During the COVID-19 Lockdown. (5th November 2021) - Ozik, Gideon; Sadka, Ronnie; Shen, Siyi
Abstract: This article studies the impact of retail investors on stock liquidity during the COVID-19 pandemic lockdown in spring 2020. Retail trading exhibits a sharp increase, especially among stocks with high COVID-19–related media coverage. Retail trading attenuated the rise in illiquidity by roughly 40% but less so for high-media-attention stocks. Causality is addressed using the staggered implementation of the stay-at-home advisory across U.S. states. The results highlight that ample free time and access to financial markets facilitated by fintech innovations to trading platforms are significant determinants of retail-investor stock market participation.